Accessing primary healthcare during COVID-19: health messaging during lockdown. (2nd January 2022) - Blake, Denise; Thompson, Jessica; Chamberlain, Kerry; McGuigan, Kathryn
ABSTRACT: Accessing healthcare during a disaster matters for the well-being of people and communities. This article explores healthcare messaging about General Practitioner (GP) services for non-COVID-19 health concerns during the Level 4 lockdown in Te Papaioea (Palmerston North), Aotearoa New Zealand. Messaging from Government, media and local GP clinics were analysed to understand how people were advised to seek care for non-COVID-19 health concerns. We found inconsistencies in these communications, ranging from messages to not attend healthcare services because of possible COVID-19 surges, to messages with vague, or lack of, information. Government messages did include advice for seeking general healthcare, but this was largely rendered invisible due to the focus on 'staying home, saving lives'. Media messaging was similarly influenced by these Government directives. Few GP clinics had websites, and few provided information about accessing general healthcare services. Clinics also lacked up-to-date telephone messages about seeking healthcare for non-COVID-19 symptoms and illnesses. All three sources neglected the cultural, social and contextual diversity of the local audience. We recommend that communication during disasters should be clear, concise and consistent. Further, GPs should be supported to have websites and telecommunication platforms. All communications should be inclusive and aim to reach diverse audiences.